Dispersive mixing efficiency of an elongational flow mixer on PP/EPDM blends: Morphological analysis and correlation with viscoelastic properties. Issue 6 (31st July 2013) - Rondin, Jérôme; Bouquey, Michel; Muller, René; Serra, Christophe A.; Martin, Grégory; Sonntag, Philippe
<x xml:space="preserve">Abstract</x> Polypropylene and ethylene‐propylene‐diene terpolymer (PP/EPDM) blends were melt compounded in a new mixing device, designed in our laboratory under the trademark of RMX®, which predominantly generates elongational flows. Dispersion of the EPDM minor phase in PP was carried out in both RMX® and in an internal mixer (Haake Rheomix 600) at equivalent specific mixing energies and the resultant morphologies obtained by SEM were analyzed and compared. A better dispersive mixing efficiency of the RMX® mixer, i.e., lower Dn and Dv of the dispersed EPDM phase was observed. The impact of elongational flow was more pronounced for blends having a high viscosity ratio p, indicating an enhanced droplet break‐up mechanism, which was attributed to the combination of high shear rates inside the mixing element and important elongational flows in the convergent/divergent zones. The morphology of the blends was correlated with their linear viscoelastic properties by using the Palierne model. Very good agreement was found for the PP/EPDM 80/20 blends but for higher EPDM content, the Palierne model failed to describe the rheological behavior, which was attributed to percolation of the minor phase with increasing the concentration. Higher elasticity at low frequencies was observed for blends processed in the RMX®, which was attributed to a higher generated interfacial area. POLYM. ENG. SCI., 54:1444–1457, 2014. © 2013 Society of Plastics Engineers